Sugar metabolism and the plant target of rapamycin kinase: a sweet operaTOR? - Dobrenel, Thomas; Marchive, Chloé; Azzopardi, Marianne; Clément, Gilles; Moreau, Manon; Sormani, Rodnay; Robaglia, Christophe; Meyer, Christian (Frontiers in Plant Science, 2013)
In eukaryotes, the ubiquitous TOR (target of rapamycin) kinase complexes have emerged as central regulators of cell growth and metabolism. The plant TOR complex 1 (TORC1), that contains evolutionary conserved protein partners, has been shown to be implicated in various aspects of C metabolism. Indeed Arabidopsis lines affected in the expression of TORC1 components show profound perturbations in the metabolism of several sugars, including sucrose, starch, and raffinose. Metabolite profiling experiments coupled to transcriptomic analyses of lines affected in TORC1 expression also reveal a wider deregulation of primary metabolism. Moreover recent data suggest that the kinase activity of TORC1, which controls biological outputs like mRNA translation or autophagy, is directly regulated by soluble sugars.